2020
DOI: 10.5606/archrheumatol.2020.7174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single-Task Versus Dual-Task Training on Balance Performance in Elderly Patients With Knee Osteoarthritis

Abstract: Objectives: This study aims to compare the effects of single-task and dual-task training on balance performance in elderly patients with knee osteoarthritis (OA). Patients and methods: Fifty elderly osteoarthritic patients with balance impairment (16 males, 34 females; mean age 72.9±5.5 years; range 65 to 84 years) were included in this study. Patients were randomly assigned to single-task balance training (group 1) or dual-task balance training (group 2) groups. Balance activities were given to both groups fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…31 In this present study, the post-intervention dynamic balance improved in the exercise group as measured by the TUG. Our finding was in line with UzunkulaoGlu et alwho recently illustrated that the balance training with tandem movements improved from 13.2 to11.2 s. 32 Moreover, the time spent for TUG in the present study was lower than those previously reported fall risk cut-off points . 33,34 In conclusion, these findings suggested that 30-minute SEBT exercise training 3 times/week for 4 weeks was efficient to improve static and dynamic balance in the persons with the unilateral OA knee.…”
Section: Discussionsupporting
confidence: 93%
“…31 In this present study, the post-intervention dynamic balance improved in the exercise group as measured by the TUG. Our finding was in line with UzunkulaoGlu et alwho recently illustrated that the balance training with tandem movements improved from 13.2 to11.2 s. 32 Moreover, the time spent for TUG in the present study was lower than those previously reported fall risk cut-off points . 33,34 In conclusion, these findings suggested that 30-minute SEBT exercise training 3 times/week for 4 weeks was efficient to improve static and dynamic balance in the persons with the unilateral OA knee.…”
Section: Discussionsupporting
confidence: 93%
“…The 38 identified RCTs investigated various individual (aerobic 35,51,57 , (aquatic 42,43 , neuromuscular 39,47 , resistancebased, 38,44,45 ) and combined 37,41,46 exercise-therapies/physical activities, technologies (telerehab 48,50 , video games 40 ) and behaviour change approaches 49 to improve adherence to exercise and PA, modalities (cryotherapy 54,68 , electrical current therapy 53 , ESWT 62 , interferential current 61 , laser 32 , pneumatic compression 58 , transcutaneous electrical nerve stimulation 60 and therapeutic ultrasound 59 ), manual (acupressure 65 , mobilization with movement 66,67 , neurodynamic mobilizations 34 ), needling 36,52 , taping 33,63,64 , or combined 55,56,69 therapies.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“…In knee OA patients an effective assessment of balance control is necessary before management of condition. 7 Aslihan in 2020 compared effect of performance of single versus dual task exercise on balance in elderly persons with knee osteoarthritis (KOA). They concluded that dual task exercises was not superior to single task exercises for improving balance in knee OA patients.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that dual task exercises was not superior to single task exercises for improving balance in knee OA patients. 7 In 2019 Gulsen reported that greater numbers of falls in older people with knee osteoarthritis (KOA) has been experienced by participants with no OA. Balance tests were applied with Tetrax Interactive Balance System, Berg Balance Scale (BBS) was applied formeasured the balance of patients.…”
Section: Introductionmentioning
confidence: 99%